Pengaruh Penggunaan E-Learning Edmodo Terhadap Hasil Belajar dan Persepsi Siswa Tentang Pembelajaran Daring di SMP Avisena Jabon - Pramesti, Windi Ayu; Shofiyah, Noly (Indonesian Journal of Science Learning (IJSL), 2021)
This study aims to determine the effect of the use of E-learning Edmodo on learning outcomes and to determine the effect of E-learning Edmodo on students’ perceptions of online learning. Pre-experimental quantitative research method with a one group pretest-posttest design research that was tested on an experimental class using an assessment instrument in the form of multiple choice test questions to determine students’ cognitive learning outcomes and a questionnaire in the form of a questionnaire to determine students’ perceptions of online learning. The population used is online class VIII students at SMP AVISENA Jabon. The effect of the use of the Edmodo E-learning platform on the cognitive learning outcomes of online class VIII students at SMP AVISENA Jabon. The results of the t-test analysis using paired simple t-test obtained a significant value of 0.000 which is smaller than a significant level of 0.05; So it can be interpreted that the experimental class has changes in students’ cognitive learning outcomes after using the Edmodo E-learning platform. While the effect of using the Edmodo E-learning platform on students’ perceptions of online learning, the results of the t-test analysis using paired simple t-test obtained a significant value of 0.000 which is smaller than the significant level of 0.05; So that it can be interpreted that the experimental class has a change in students’ perceptions of online learning by being given treatment in the implementation of learning using the Edmodo E-learning platform. So it can be concluded that the use of the Edmodo E-learning platform affects students’ cognitive learning outcomes and can affect students’ perceptions of online learning in class VIII online SMP Avisena Jabon.